Application aware routing protocol for wireless mesh networks (WMNs) - Bari, S. M. Sadakatul (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
IEEE 802.11s amendment of mesh networking set hybrid wireless mesh protocol (HWMP) as the default path selection protocol at layer-2 (MAC layer) and airtime link metric (ALM) as default routing metric. ALM accounts the channel resources used to transmit a frame over a particular link. However, this routing metrics assumes that all applications running in the internet have the same requirement ignoring the fact that different applications have different characteristics. For example, voices are delay and loss sensitive, video applications are delay sensitive but packet loss tolerant to some extent. On contrary, E-mail applications are delay tolerant but loss sensitive. So these should be considered in designing routing metrics to improve the network performance. This dissertation first compares layer-2 (HWMP) and layer-3 (Ad-hoc on Demand Distant Vector) routing protocol to see the effect of routing at these two layers. Secondly the problem associated with airtime link metrics is discussed and this metrics is enhanced by introducing priority parameter based on the application. The priority metrics are incorporated with HWMP protocol and named HWMP-AppAware. Simulations have been carried out to evaluate the performance of the proposed enhancement. Simulation results show that HWMP-AppAware demonstrates better performance in comparison with standard HWMP protocols with respect to throughput, packet delivery ratio, average end-to-end delay and average jitter. The proposed HWMP-AppAware shows an improvement of network throughput 22.64% for VoIP, 22.67% for FTP and 16.20% for HTTP compared to HWMP-Proactive protocol. However, the throughput decreases 6.7% for video traffic. Packet delivery ratio (PDR) improved 23.92% for VoIP, 21.67% for FTP and 15.20% for HTTP compared to HWMP-Proactive protocol. However, packet delivery ratio decreases 10.43% for video traffic. The Average end-to-end delay reduced 19.92% for VoIP, 32% for Video and 8.9% for FTP compared to HWMP-Proactive protocol. However, delay increases 6.7% for HTTP. Average jitter also reduced 9.02% for VoIP, 22% for Video and 17% for FTP compared to HWMP-Proactive protocol. However, Average jitter increases 11% for HTTP.